On linear combinations of L-orthogonal polynomials associated with distributions belonging to symmetric classes - Batelo, M. A.; Bracciali, Cleonice Fátima [UNESP]; Ranga, A. S. (Elsevier B.V., 2005)
This paper deals with the classes S-3(omega, beta, b) of strong distribution functions defined on the interval [beta(2)/b, b], 0 < beta < b <= infinity, where 2 omega epsilon Z. The classification is such that the distribution function psi epsilon S-3(omega, beta, b) has a (reciprocal) symmetry, depending on omega, about the point beta. We consider properties of the L-orthogonal polynomials associated with psi epsilon S-3(omega, beta, b). Through linear combination of these polynomials we relate them to the L-orthogonal polynomials associated with some omega epsilon S-3(1/2, beta, b). (c) 2004 Elsevier B.V. All rights reserved.
Keywords: L-orthogonal polynomials; symmetric distribution functions; Three term recurrence relations